NEPHROPROTECTIVE ACTIVITY OF ETHANOL EXTRACT OF KIRINYUH (CHROMOLAENA ODORATA L) IN GENTAMICIN INDUCED NEPHROTOXICITY IN WISTAR RATS - IDACAHYATI, KENI; NURDIANTI, LUSI; HUSNI, SILVI SIPTANUL; GUSTAMAN, FIRMAN; WULANDARI, WINDA TRISNA (International Journal of Applied Pharmaceutics, 2021)
Objective: The global prevalence of Chronic Kidney Disease (CKD) was 9.1% (697.5 million cases). Chronic kidney disease can occur, one of which is caused by drug nephrotoxicity. Nephrotoxicity remains major problem for its effective long-term clinical use. Gentamicin is known to cause many morphologic, metabolic and functional alterations in the kidney and the specificity of gentamicin nephrotoxicity is related to its accumulation in the renal proximal convoluted tubules leading to tubular necrosis. Nephrotoxicity can be prevented by nephroprotective by giving antioxidants. Kirinyuh leaves (Chromolaena odorata L.) has potential as a nephroprotective because it contains chemical compounds that have antioxidant activity. Methods: Wistar rats as many as 25 animals were divided into five groups, namely the normal control negative control (gentamicin 60 mg/kg BW rat), and kirinyuh leaf extract at a dose of 225, 450 and 675 mg/kg BW treatment was carried out for 10 d. Serum creatinine and urea levels were evaluated along with histopathological investigation in various experimental groups of rats. Data analysis using the One Way Anova test and continued LSD test. Results: Serum creatinine was a significant difference between groups P = 0.000 (P<0.05). The results of LSD analysis on creatinine levels showed a significant difference between the normal group and the negative group (P = 0.00); negative group to dose group 1 (P = 0.020) (P<0.05); dose 2 (P = 0.005) (P<0.05); and dose 3 (P = 0.000) (P<0.05). Dose 3 had the lowest creatinine level compared to other dose groups. Conclusion: Serum creatinine level at dose 675 significantly changes compare by a negative group of other dose groups. Renal histopathology results showed that the group with a dose of 450 mg/BW of rats had the lowest necrosis rate compared to the negative control group and other dose groups.